Assessing Coverage of Population-Based and Targeted Fortification Programs with the Use of the Fortification Assessment Coverage Toolkit (FACT): Background, Toolkit Development, and Supplement Overview. Issue 5 (12th April 2017) - Friesen, Valerie M; Aaron, Grant J; Myatt, Mark; Neufeld, Lynnette M
Abstract: Food fortification is a widely used approach to increase micronutrient intake in the diet. High coverage is essential for achieving impact. Data on coverage is limited in many countries, and tools to assess coverage of fortification programs have not been standardized. In 2013, the Global Alliance for Improved Nutrition developed the Fortification Assessment Coverage Toolkit (FACT) to carry out coverage assessments in both population-based (i.e., staple foods and/or condiments) and targeted (e.g., infant and young child) fortification programs. The toolkit was designed to generate evidence on program coverage and the use of fortified foods to provide timely and programmatically relevant information for decision making. This supplement presents results from FACT surveys that assessed the coverage of population-based and targeted food fortification programs across 14 countries. It then discusses the policy and program implications of the findings for the potential for impact and program improvement.